JUH-1H Redesigned Pneumatic Boot Deicing System Flight Test Evaluation - Graham, Matthew S; Haworth, Loran A; Kimberly, Jack L (1987)
The U.S. Army Aviation Engineering Flight Activity conducted an evaluation of the Pneumatic Boot Deicing System (PBDS) with two pneumatic deicer boot designs, referred to as second and third generation. The objective of the test was to conduct feasibility testing of the pneumatic system concept for deicing helicopter rotor blades in forward flight, and to assess any changes to aircraft performance and handling qualities. Phase I consisted of a ground and inflight structural loads survey which established an operational envelope. Phase 2 consisted of forward flight testing in artificial and natural icing conditions of the second generation design only. Phase 3 consisted of limited artificial rain erosion tests of the second generation design. Phase 4 consisted of performance and handling qualities evaluation of the second generation design. Hover and level flight performance were greatly improved over the first generation, but a significant performance penalty still exists. Handling qualities were essentially unchanged from the standard UH-1H. Two unsatisfactory and six undesirable reliability and maintainability characteristics were identified.